Ответы и объяснения

Лучший Ответ!
2012-02-14T17:02:32+00:00

- х - ( 1,5 - 4 ) = 6,7

- х - 1,5 + 4 - 6,7 = 0

- х - 4,2 = 0

- х = 4,2

х = - 4,2

2012-02-14T19:16:17+00:00

-х-(1,5-4)=6,7                                                                                                               -х-1,5+4-6,7=0                                                                                                             -х-4,2=0                                                                                                                      -х=4,2                                                                                                                           х=-4,2